Oropharyngeal cancer: First relapse description and prognostic factor of salvage treatment according to p16 status, a GETTEC multicentric study. (January 2021) - Culié, Dorian; Lisan, Quentin; Leroy, Charlotte; Modesto, Anouchka; Schiappa, Renaud; Chamorey, Emmanuel; Dassonville, Olivier; Poissonnet, Gilles; Guelfucci, Bruno; Bizeau, Alain; Vergez, Sebastien; Dupret-Bories, Agnes; et al.
Abstract: Introduction: Although Human Papilloma Virus (HPV)-driven oropharyngeal cancer (OPC) prognosis is significantly better than that of other head and neck cancers, up to 25% of cases will recur within 5 years. Data on the pattern of disease recurrence and efficiency of salvage treatment are still sparse. Material and method: Observational study of all recurrent OPCs diagnosed, following a curative intent treatment, in seven French centers from 2009 to 2014. p16 Immunohistochemistry was used to determine HPV status. Clinical characteristics, distribution of recurrence site, and treatment modalities were compared by HPV tumor status. Overall survival was examined using Kaplan–Meier and multivariate Cox regression modeling. Results: 350 recurrent OPC patients (246 p16-negative and 104 p16-positive patients). The site of recurrence was more frequently locoregional for p16-negative patients (65.4% versus 52.9% in p16-positive patients) and metastatic for p16-positive patients (47.1% versus 34.6% in p16-patients, p  = 0.03). Time from diagnosis to recurrence did not differ between p16-positive and p16-negative patients (12 and 9.6 months, respectively, p -value = 0.2), as the main site of distant metastasis (all p -values ≥0.10). Overall and relapse-free survival following the first recurrence did not differ according to p16 status ( p -values from log-rank 0.30 and 0.40, respectively). In multivariate analysis, prognosis factors for overall survival in p16-negative patients were distant metastasis (HR 2.11, 95% CI 1.30–3.43) and concurrent local and regional recurrences (HR 2.20, 95% CI 1.24–3.88). Conclusion: With the exception of the initial site of recurrence, the pattern of disease relapse and the efficiency of salvage treatment are not different between p16-positive and negative OPCs. Highlights: Site of recurrence was more frequently locoregional for p16-negative patients. Site of recurrence was more frequently metastatic for p16-positive patients. Time from diagnosis to recurrence did not differ according to p16 status. The main site of distant metastasis did not differ either according to p16 status. Overall survival after the first recurrence did not differ according to p16 status.